Over‐the‐scope clip versus transcatheter arterial embolization for refractory peptic ulcer bleeding—A propensity score matched analysis. Issue 9 (25th August 2021) - Kuellmer, Armin; Mangold, Tobias; Bettinger, Dominik; Maruschke, Lars; Wannhoff, Andreas; Caca, Karel; Wedi, Edris; Hosseini, Ali Seif Amir; Kleemann, Tobias; Schulz, Thomas; Jung, Carlo; Thimme, Robert; et al.
Abstract: Background: Transcatheter arterial embolization (TAE) or surgery are standard treatment of peptic ulcer bleeding (PUB) refractory to endoscopic hemostasis. Over‐the‐scope clips (OTSC) have shown superiority to standard endoscopic treatment. Objective: To compare OTSC treatment to TAE in refractory peptic ulcer bleeding. Patients and Methods: In this retrospective, multicenter study, 128 patients treated with OTSC ( n = 66) or TAE ( n = 62) for refractory PUB between 2009 and 2019 in four academic centers were analyzed. Primary endpoint was clinical success (hemostasis + no rebleeding within 7 days). Secondary endpoints were adverse events, length of ICU stay, and mortality. Propensity score matching was performed to adjust for differences in baseline characteristics. Results: Patients characteristics were similar in both groups but ulcers in the TAE group were larger, more often located in the duodenal bulb (85.5% vs. 65.2%; p = 0.014), and that the proportion of Forrest Ia bleedings was higher (38.7% vs. 19.7%; p = 0.018). Clinical success was comparable in both groups (74.2% vs. 59.7%; p = 0.092). Stay on the intensive care unit (ICU) was significantly longer in the TAE group (mean 8.0 vs. 4.7 days; p = 0.002). Serious adverse events after re‐therapy (12.9% vs. 1.5%; p = 0.042) and in‐hospital mortality were significantly higher in the TAE group (9.1 vs. 22.6%, OR 2.92 [95% CI 1.04–8.16]; p = 0.05). After propensity score matching, the differences found regarding ICU stay (4.9± 5.9 and 9.2 ± 11.2; p = 0.009) and in‐hospital mortality (5% vs. 22.5%; OR 5.52 [95% CI: 1.11–27.43]; p = 0.048) stayed significant. Conclusions: OTSC treatment for refractory PUB was superior to TAE in terms of ICU stay and in‐hospital mortality.